Problem of sense in the classical philosophical tradition: socio-cultural aspect - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the socio-cultural analysis of philosophical concepts, exploring the category of sense as a given, present in thetranscendental realm.